Core-shell slow-release tackifier as well as preparation method and application thereof
By designing a core-shell sustained release viscosity enhancer, using high-temperature hydrophobic branch chains and hydrophobic monomers, combined with a temperature-resistant polymer shell, the problems of high-temperature and high-density cement slurry settlement and insufficient temperature resistance of viscosity enhancer are solved, and the problem of low temperature and high-density cement slurry settlement and viscosity enhancer resistance is achieved. The stable suspension stability at high temperature and the slurry consistency without affecting low temperature meet the construction needs of 150℃~210℃.
Patent Information
- Application Number
- CN202310780627.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-06-28
AI Technical Summary
The prior art medium and high temperature high density cement slurry is prone to settle, the viscosity enhancer is insufficient to resist temperature and thicken the low temperature and becomes thinner in high temperature, making it difficult to maintain stability in ultra-high temperature environments.
Design a core-shell sustained release viscosity enhancer. By introducing high-temperature resistant hydrophobic branch chains and hydrophobic monomers, it is wrapped in a polymer shell with a certain temperature resistance ability to form a core-shell structure to avoid high temperature of polymer viscosity enhancers Decompose and thinn up and avoid thickening at low temperatures.
The shell material above 90℃ decomposes and releases the core viscosity enhancer, providing high temperature stability and low temperature without significant impact, the maximum temperature resistance reaches 210℃, and the difference in the standing density of the cement slurry after maintenance is less than 0.03g/cm3, meeting 150℃~ High temperature construction environment of 210℃.
Smart Images

Figure CN119220232A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oilfield chemistry, and in particular to a core-shell slow-release tackifier and a preparation method and application thereof. Background Art
[0002] As oil exploration and development continues to develop towards deep and ultra-deep wells, high-temperature and high-pressure formation environments have become an inevitable challenge for cementing projects. Under high temperatures, the Brownian motion of cement particles intensifies, resulting in a decrease in viscosity, which leads to self-settling; in high-temperature and high-pressure environments, high-density cement slurry systems are often configured. High-density cement slurries contain a large amount of weighting materials such as iron powder, making it difficult to control the stability of settlement; in high-temperature environments, too much retarder is often added, resulting in a strong dispersion of the slurry itself, which further destroys the stability of settlement.
[0003] At present, the method of reducing the water-cement ratio and reducing the amount of retarder and dispersant used in on-site construction is often used to improve the high-temperature stability of the slurry. However, this method will make the initial viscosity of the cement slurry too high, affecting the normal pumping of the cement slurry. Researchers have found that optimizing the particle size composition of solid particles in the cement slurry and increasing the solid content per unit volume can improve the stability of the slurry. However, this method has high processing costs, complex processes, and is limited by cementing materials and site requirements. It is not easy to implement and has certain limitations in improving the sedimentation stability of cement slurry. In addition, the addition of some inorganic suspension stabilizers including silica fume, metakaolin, hollow microspheres, microsilica, fine sand, volcanic ash, lime, mineral fillers, clay, nanomaterials, etc. can improve the suspension stability of the slurry. However, the addition of some inorganic materials will have an adverse effect on the strength development of cement stone. In addition, polymer stabilizers are currently widely used and have good suspension stability, but polymer viscosity enhancers tend to thicken the slurry at low temperatures and are difficult to pump. At high temperatures, polymer materials decompose and make the slurry thinner (thickening at low temperatures and thinning at high temperatures), which still cannot solve the problem of settlement instability of high-temperature and high-density cement slurry. Therefore, it is urgent to develop an intelligent thickener that "does not thicken at low temperatures and increases viscosity at high temperatures".
[0004] At present, there are very few domestic sedimentation stabilizer products, most of which have a temperature resistance of around 150°C, and begin to have a viscosity-increasing effect at low temperatures, resulting in poor overall performance of cement slurry with the addition of sedimentation stabilizers.
[0005] Li Xiaolin and others designed and developed a new type of thermal viscosity-increasing copolymer containing hydrophobic monomers, and developed a high-temperature stabilizer for high-density cement slurry based on the thermal viscosity-increasing copolymer. The apparent viscosity of the thermal viscosity-increasing copolymer solution gradually increased with the increase of temperature, reaching a maximum value at 1151125℃. As the temperature continued to rise, the apparent viscosity decreased slightly, but the apparent viscosity at 150℃ could still be maintained at 214 times the initial apparent viscosity, showing a good thermal viscosity-increasing effect. 1% thermal viscosity-increasing copolymer was introduced into 2.50g / cm 3In high-density cement slurry, the density difference of cement slurry at 150℃ is 0.58g / cm 3 , reduced to 0.07g / cm 3 , the density difference of cement stone is reduced to 0.08g / cm 3 The comprehensive performance can meet the needs of on-site construction. However, the temperature resistance of the system is only 150°C, which is far from the actual ultra-high temperature target, and the polymer has a certain viscosity at low temperature. For details, see [Li Xiaolin, Li Jianhua, Yang Hongbin, et al. High-temperature stabilizer of high-density cement slurry based on thermal viscosity-increasing copolymer [J]. Drilling Fluids and Completion Fluids, 2022, 39(1)76-81.]
[0006] Xiong Zhengqiang et al. proposed to use lithium soap as an ultra-high temperature thickener for water-based drilling fluid. The experimental results show that synthetic lithium soap H-6 has excellent viscosity-increasing performance and thermal stability, and its temperature resistance can reach 240°C, and its high temperature resistance and viscosity-increasing effect are better than the existing high temperature thickener products at home and abroad. When 1% H-6 is added to 4% sodium bentonite-based slurry, the apparent viscosity of the slurry before and after aging at 240°C for 16 hours is 16.5mPa·s, while the apparent viscosity reduction rate of the sodium soil-based slurry with 1% high temperature thickener HE300 after aging at 240°C for 16 hours is greater than 92%. The research results show that synthetic lithium soap has good compatibility with other treatment agents, is suitable for use as an ultra-high temperature thickener, and has broad application prospects in ultra-high temperature water-based drilling fluids. However, there is currently no research in high temperature cement slurry systems. For details, please refer to [Xiong Zhengqiang, Li Xiaodong, Fu Fan, et al. Experimental study on synthetic lithium laponite as a viscosity enhancer for ultra-high temperature water-based drilling fluids [J]. Drilling Fluids and Completion Fluids, 2018, 35(5): 19-25.]
[0007] Chinese patent CN106967397B discloses a cellulose hydrophobically modified thermal thickener, wherein cellulose is dissolved in an alkaline solution, stirred evenly, a soluble salt is added, high molecular weight cellulose is precipitated, alkylene oxide is added for etherification reaction, and the product is then subjected to hydrophobic modification reaction with a long-chain halogenated alkane to obtain a cellulose hydrophobically modified thermal thickener. The product can play a viscosity-enhancing role at around 40°C, the test temperature of the system is 150°C, and the water-cement ratio is 0.4, which belongs to a conventional density system, and a high-temperature and high-density system is difficult to achieve.
[0008] Chinese patent CN108586671B discloses an anionic thermal thickening water-soluble polymer and a preparation method thereof. Acrylamide, acrylic acid and Pluronic triblock polymers are used for inverse emulsion polymerization. The molecular weight of the thermal thickening polymer is increased by the high reactivity of acrylamide and inverse emulsion polymerization, and a significant thermal thickening effect can be produced at low concentrations, which can reduce the application cost; the dissolution rate of the obtained polymer emulsion is significantly faster than the dissolution rate of the polymer dry powder; the obtained emulsion dilution has a strong thermal thickening behavior after adding a small amount of inverse agent again, and the emulsion dilution has different thermal thickening behaviors as the amount of inverse agent added increases. However, the thickening agent begins to increase viscosity at around 40°C, which will make low-temperature pumping difficult.
[0009] Chinese patent document CN115872647A discloses a suspension stabilizer, which is a composite calcined product made of attapulgite, sepiolite and nano-silicon dioxide. The operating temperature of the stabilizer is 30°C-1180°C, indicating that viscosity has begun to increase at low temperatures, which is not conducive to the pumping of cement slurry, and cannot be used at high temperatures (>200°C).
[0010] At present, the existing literature on cement slurry thickeners are all applied in environments below 200°C, and the problem of low-temperature thickening has not been solved. Summary of the invention
[0011] The present invention aims at the problem of easy sedimentation of high-temperature and high-density cement slurry systems in the prior art, as well as the problems of insufficient temperature resistance, low-temperature thickening, and high-temperature thinning of existing thickeners. The present invention proposes a core-shell slow-release thickener, which first introduces high-temperature resistant hydrophobic side chains (AMPS and hydrophobic monomers) through molecular structure design to avoid the problem of high-temperature decomposition and thinning of polymer thickeners; then wraps it inside a polymer shell with a certain temperature resistance to obtain a core-shell slow-release thickener to solve the problem of low-temperature thickening.
[0012] To solve the above technical problems, the first aspect of the present invention provides a core-shell sustained-release thickener, including a core material and a shell material, wherein the core material is prepared from a raw material I including 2-acrylamide-2-methylpropane sulfonic acid (AMPS), acrylic acid (AA), a hydrophobic monomer and laponite; the shell material is prepared from a raw material II including a styrene monomer. Among them, 2-acrylamide-2-methylpropane sulfonic acid has good temperature resistance, acrylic acid has good adsorption, and laponite, as an inorganic heat-resistant material, cooperates with hydrophobic monomers to enhance the temperature resistance of 2-acrylamide-2-methylpropane sulfonic acid; the present invention optimizes the molecular structure of the thickener, improves its own temperature resistance, and then uses the prepared thickening polymer as a core material, and then preferably forms a heat-resistant core-shell sustained-release thickener with a core-shell structure, so that the core-shell sustained-release thickener is decomposed at more than 90°C of the shell material, and the core thickener is slowly released to avoid low-temperature thickening.
[0013] According to some embodiments of the present invention, the mass ratio of 2-acrylamido-2-methylpropane sulfonic acid, acrylic acid, hydrophobic monomer, and laponite is (25-60):(20-50):(10-20):(1-5), for example, 25:25:12:5, 60:50:10:1, 50:20:20:2, 25:30:15:3, 40:40:15:2.
[0014] According to some embodiments of the present invention, the hydrophobic monomer is selected from at least one of isooctyl acrylate, octadecyl acrylate, octadecyl polyoxyethylene methacrylate, behenyl polyoxyethylene ether methacrylate, and hexadecyl dimethyl allyl ammonium chloride (DMDAC-16).
[0015] According to some embodiments of the present invention, the raw material I further includes a first initiator; preferably, the first initiator is selected from at least one of ammonium persulfate and potassium persulfate.
[0016] According to some embodiments of the present invention, the raw material II also includes an emulsifier, a second initiator, and a demulsifier; preferably, the emulsifier is selected from at least one of sodium dodecyl sulfate, sodium dodecyl sulfonate, and hexadecyltrimethylammonium bromide, preferably sodium dodecyl sulfate; the second initiator is selected from at least one of ammonium persulfate and potassium persulfate, preferably potassium persulfate; the demulsifier is selected from at least one of aluminum sulfate, calcium chloride, and magnesium chloride, preferably aluminum sulfate.
[0017] The second aspect of the present invention provides a method for preparing the above-mentioned core-shell sustained-release viscosity increasing agent, comprising the following steps:
[0018] 1) mixing raw material I with water, and performing reaction I to obtain a core material;
[0019] 2) The core material obtained in step 1) is mixed with styrene monomer, and reacted in an inert atmosphere to obtain the core-shell sustained-release tackifier.
[0020] According to some embodiments of the present invention, in step 1), the ratio of raw material I to water is (184-292) g:250 mL, for example 268 g:250 mL, 242 g:250 mL, 184 g:250 mL, 292 g:250 mL, 194 g:250 mL.
[0021] According to some embodiments of the present invention, in step 1), the mixing obtains solution A, and a pH adjuster is used to adjust the pH of solution A to 7; preferably, the pH adjuster is selected from at least one of a sodium hydroxide solution and a potassium hydroxide solution with a mass fraction of 10% to 30%, for example, 10%, 20%, 30%.
[0022] According to some embodiments of the present invention, in step 1), a first initiator is further added to the reaction I; preferably, the amount of the first initiator added is 0.1% to 0.5% of the total mass of the raw material I, for example 0.1%, 0.2%, 0.3%, 0.5%.
[0023] According to some embodiments of the present invention, in step 1), the conditions of reaction I include: temperature of 30°C to 60°C, for example 45°C, 60°C, 30°C, and time of 2h to 10h, for example 2h, 4h, 5h, 6h, 10h.
[0024] According to some embodiments of the present invention, in step 1), the reaction I further comprises drying and crushing; preferably, the drying conditions include: temperature of 60° C., time of 1 h to 3 h, for example, 1 h, 2 h, 3 h.
[0025] According to some embodiments of the present invention, in step 2), the mass of the core material is 20% to 50% of the mass of the styrene monomer, for example 20%, 30%, 40%, 45%, 50%.
[0026] According to some embodiments of the present invention, in step 2), an emulsifier and a second initiator are further added to the reaction II; preferably, the amount of the emulsifier added is 1% to 8% of the mass of the styrene monomer, for example 1%, 5%, 8%; the amount of the second initiator added is 0.1% to 0.5% of the mass of the styrene monomer, for example 0.1%, 0.2%, 0.3%, 0.4%, 0.5%.
[0027] According to some embodiments of the present invention, in step 2), after the reaction II, a demulsifier is further added; preferably, the amount of the demulsifier added is 0.05% to 0.2% of the mass of the styrene monomer, for example 0.05%, 0.1%, 0.2%.
[0028] According to some embodiments of the present invention, in step 2), the conditions of reaction II include: reaction temperature of 70°C to 80°C, such as 75°C, 70°C, 80°C, and reaction time of 2h to 5h, such as 3h.
[0029] According to some embodiments of the present invention, in step 2), the inert atmosphere is selected from nitrogen.
[0030] According to some embodiments of the present invention, the core material further comprises a modification step; preferably, the modification step comprises adding a surfactant to the core material aqueous solution, and performing reaction III to obtain the modified core material.
[0031] According to some embodiments of the present invention, the water-soluble mass fraction of the core material is 10% to 50%, for example, 10%, 20%, 30%, 40%, 50%.
[0032] According to some embodiments of the present invention, the added amount of the surfactant is 10% to 40% of the mass of the core material, for example 10%, 20%, 30%, 40%; preferably, the surfactant is selected from at least one of sodium dodecyl sulfate, sodium dodecyl sulfonate, hexadecyltrimethylammonium bromide (CTAB), sodium hexadecyl sulfonate, and sodium hexadecylbenzene sulfonate.
[0033] According to some embodiments of the present invention, the core material aqueous solution further comprises a heating step; preferably, the heating temperature is 50°C to 70°C, for example, 50°C, 60°C, or 70°C.
[0034] According to some embodiments of the present invention, the conditions of reaction III include: reaction temperature of 80° C., reaction time of 2 h to 5 h, for example, 2 h, 3 h, 4 h, 5 h.
[0035] According to some embodiments of the present invention, after reaction III, the step of filtering the reaction solution, adding a precipitant to the filtrate to generate a precipitate, and drying the precipitate is further included; preferably, the amount of the precipitant added is 30% to 50% of the mass of the core material, preferably 40%; further preferably, the precipitant is at least one of a AgNO3 solution and a polyaluminium chloride solution; further preferably, the concentration of the AgNO3 solution or the concentration of the polyaluminium chloride solution is 0.05 mol / L to 0.2 mol / L, for example 0.05 mol / L, 0.1 mol / L, 0.02 mol / L.
[0036] A third aspect of the present invention provides a use of the core-shell slow-release tackifier in cementing oil and gas wells.
[0037] According to some embodiments of the present invention, the core-shell slow-release tackifier is used as a suspension stabilizer in high-density cement slurry for oil and gas well cementing. More preferably, the amount of the core-shell slow-release tackifier added to the high-density cement slurry is 1% to 5% based on the total mass of cement. The low temperature has no significant effect on the consistency of the cement slurry. The core-shell slow-release tackifier of the present invention begins to increase viscosity at 90°C, and the highest temperature resistance reaches 210°C. The density difference of the cement slurry after curing is less than 0.03g / cm after standing for two hours. 3 .
[0038] Beneficial effects:
[0039] The present invention provides a core-shell slow-release tackifier with a thermal tackifying effect. The core-shell slow-release tackifier is used as a suspension stabilizer for high-density cement slurry, which can meet the high-temperature construction environment of 150°C to 1210°C. The density difference of the cement slurry after curing is less than 0.03g / cm after standing for two hours. 3 .
[0040] The present invention provides a core-shell slow-release thickener with thermal thickening effect, which can overcome the problems of traditional suspension stabilizers thickening at low temperatures and thinning at high temperatures, and can improve cementing quality and safety.
[0041] The core-shell sustained-release tackifier provided by the present invention has a size of micron-level microspheres (1 μm-5 μm), is easy to ash at room temperature, and has little effect on the consistency of the slurry. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a SEM photograph of the core-shell sustained-release viscosity enhancer D1 prepared in Example 1 of the present invention.
[0043] Figure 2 This is a SEM photograph of the core-shell sustained-release viscosity enhancer D6 prepared in Example 6 of the present invention.
[0044] Figure 3 This is a TEM photo of the core-shell sustained-release viscosity enhancer D1 prepared in Example 1 of the present invention.
[0045] Figure 4 This is a TEM photo of the core-shell sustained-release viscosity enhancer D6 prepared in Example 6 of the present invention.
[0046] Figure 5 This is the thermogravimetric curve of the core-shell sustained-release viscosity enhancer D11D6 prepared in Examples 1-6 of the present invention.
[0047] Figure 6 This is the thermogravimetric curve of the tackifier M11M3 prepared in Comparative Examples 1-3 of the present invention.
[0048] Figure 7 This is the thickening curve of the core-shell sustained-release thickener D1 prepared in Example 1 of the present invention.
[0049] Figure 8 This is the thickening curve without adding the core-shell sustained-release thickener D1 prepared in Example 1 of the present invention.
[0050] Fig. 9 This is the thickening curve of the viscosity enhancer M1 prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0051] The present invention will be further described below in conjunction with the embodiments, but the present invention is not limited by these embodiments.
[0052] The 2-acrylamido-2-methylpropanesulfonic acid in the present invention was purchased from Beijing Wokai Biotechnology Co., Ltd., and the model / specification was 500 g.
[0053] Acrylic acid in the present invention was purchased from Beijing Inokai Technology Co., Ltd., and the model / specification was 100 mL.
[0054] The hexadecyl dimethyl allyl ammonium chloride in the present invention was purchased from Chongqing Ruiya Biotechnology Co., Ltd., and the model / specification was 25 kg.
[0055] The hectorite in the present invention was purchased from Shanghai Myrel Biochemical Technology Co., Ltd., and the model / specification was 100g.
[0056] Isooctyl acrylate in the present invention was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., and the model / specification was 100 mL.
[0057] The octadecyl acrylate in the present invention was purchased from Shanghai Myrel Biochemical Technology Co., Ltd., with a model / specification of 500 mL.
[0058] The octadecyl polyoxyethylene methacrylate in the present invention was purchased from Wuhan Hongde Yuexin Pharmaceutical Technology Co., Ltd. The model / specification is 25 kg.
[0059] The surfactant CTAB in the present invention was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., and the model / specification was 100 g.
[0060] The styrene monomer in the present invention was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., and the model / specification was 500 mL.
[0061] The three-necked bottle, four-necked flask, vacuum drying oven and crusher in the present invention are all common commercially available products unless otherwise specified.
[0062] The present invention uses a thermogravimetric analyzer (Shanghai Etissen Instrument Technology Co., Ltd., ATS-TGA-1200Q) and a pressurized thickener (Shenyang Aerospace University Application Technology Co., Ltd., double-kettle pressurized thickener).
[0063] The SEM photograph of the core-shell sustained-release tackifier material of the present invention is taken using a scanning electron microscope.
[0064] The TEM photograph of the core-shell sustained-release tackifier material of the present invention is taken using a transmission electron microscope.
[0065] Example 1
[0066] This embodiment provides a core-shell sustained-release viscosity increasing agent.
[0067] The preparation method is as follows:
[0068] (1) 100 g of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), 100 g of acrylic acid (AA), 48 g of hexadecyldimethylallylammonium chloride, and 20 g of laponite were dissolved in 250 mL of water to obtain solution A. The pH of solution A was adjusted to 7 using a 20% by mass sodium hydroxide solution. Solution A was then transferred into a three-necked flask, 0.804 g of ammonium persulfate was added, and the mixture was reacted at a constant temperature of 45° C. for 5 h. The reaction product was placed in a vacuum drying oven at 60° C. for 2 h, and then crushed into powder using a crusher to obtain a core material.
[0069] (2) 50 g of the core material prepared in step (1) was mixed with water to prepare a suspension solution with a mass fraction of 30%, and the temperature was raised to 60° C. to allow the core material to fully swell. Then, 15 g of a surfactant CTAB was added. The mixture was stirred at 80° C. and reacted at a rate of 800 r / min for 3 h. After filtration, 20 g of a 0.1 mol / L AgNO3 solution was added to the filtrate to generate a precipitate. The precipitate was dried at 80° C. for 2 h to obtain a modified core material.
[0070] (3) 45 g of the modified core material and 100 g of styrene monomer were added to a four-necked flask, and stirred at a speed of 800 r / min to fully disperse the modified core material in the styrene monomer. Then, 0.3 g of potassium persulfate and 5 g of sodium dodecyl sulfate were added at a speed of 800 r / min to obtain a stable emulsion. The emulsion polymerization reaction was carried out at a temperature of 75° C. and under the protection of a nitrogen atmosphere for 3 h. Then, 0.1 g of aluminum sulfate was added to the polymerization product under stirring to break the emulsion. The obtained precipitate was washed and dried to obtain a core-shell type tackifier material D1. The SEM photograph of D1 is shown in FIG. Figure 1 , TEM photos see Figure 3 ,from Figure 1It can be seen that the core-shell sustained-release thickener D1 has an obvious core-shell structure and a uniform size of about 1 μm to 5 μm.
[0071] Example 2
[0072] This embodiment provides a core-shell sustained-release viscosity increasing agent.
[0073] The preparation method is as follows:
[0074] (1) 120 g of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), 100 g of acrylic acid (AA), 20 g of isooctyl acrylate, and 2 g of laponite were dissolved in 250 mL of water to obtain solution A. The pH of solution A was adjusted to 7 using a 10% by mass sodium hydroxide solution. Solution A was then transferred into a three-necked flask, 0.242 g of ammonium persulfate was added, and the mixture was reacted at a constant temperature of 30° C. for 2 h. The reaction product was placed in a vacuum drying oven at 60° C. for 1 h, and then crushed into powder using a crusher to obtain a core material.
[0075] (2) 50 g of the core material prepared in step (1) was mixed with water to prepare a suspension solution with a mass fraction of 10%, and the temperature was raised to 50° C. to allow the core material to fully swell. Then, 5 g of a surfactant CTAB was added. The mixture was stirred at 80° C. and reacted at a rate of 800 r / min for 2 h. After filtration, 15 g of a 0.05 mol / L AgNO3 solution was added to the filtrate to generate a precipitate. The precipitate was dried at 80° C. for 2 h to obtain a modified core material.
[0076] (3) 20 g of the modified core material and 100 g of styrene monomer were added to a four-necked flask, and stirred at a speed of 800 r / min to fully disperse the modified core material in the styrene monomer. Then, stirring was continued at a speed of 800 r / min and 0.1 g of potassium persulfate and 8 g of sodium dodecyl sulfate were added to obtain a stable emulsion. The emulsion polymerization reaction was carried out at a temperature of 70°C and under nitrogen atmosphere protection for 3 hours. Then, 0.05 g of aluminum sulfate was added to the polymerization reaction product under stirring to break the emulsion. The resulting precipitate was washed and dried to obtain the core-shell type thickener material D2.
[0077] Example 3
[0078] This embodiment provides a core-shell sustained-release viscosity increasing agent.
[0079] The preparation method is as follows:
[0080] (1) 100 g of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), 40 g of acrylic acid (AA), 40 g of octadecyl acrylate, and 4 g of laponite were dissolved in 250 mL of water to obtain solution A. The pH of solution A was adjusted to 7 using a 30% by mass potassium hydroxide solution. Solution A was then transferred into a three-necked flask, 0.92 g of ammonium persulfate was added, and the mixture was reacted at a constant temperature of 60° C. for 10 h. The reaction product was placed in a vacuum drying oven at 60° C. for 3 h, and then crushed into powder using a crusher to obtain a core material.
[0081] (2) 50 g of the core material prepared in step (1) was mixed with water to prepare a suspension solution with a mass fraction of 30%, and the temperature was raised to 70° C. to allow the core material to fully swell. Then, 20 g of a surfactant CTAB was added. The mixture was stirred at 80° C. and reacted at a rate of 800 r / min for 3 h. After filtration, 25 g of polyaluminum chloride with a concentration of 0.1 mol / L was added to the filtrate to generate a precipitate. The precipitate was dried at 80° C. for 2 h to obtain a modified core material.
[0082] (3) 50 g of the modified core material and 100 g of styrene monomer were added to a four-necked flask, and stirred at a speed of 800 r / min to fully disperse the modified core material in the styrene monomer. Then, stirring was continued at a speed of 800 r / min and 0.5 g of potassium persulfate and 8 g of sodium dodecyl sulfate were added to obtain a stable emulsion. The emulsion polymerization reaction was carried out at a temperature of 80°C and under nitrogen atmosphere protection for 3 h. Then, 0.2 g of aluminum sulfate was added to the polymerization reaction product under stirring to demulsify the emulsion. The resulting precipitate was washed and dried to obtain a core-shell type thickener material D3.
[0083] Example 4
[0084] This embodiment provides a core-shell sustained-release viscosity increasing agent.
[0085] The preparation method is as follows:
[0086] (1) 100 g of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), 120 g of acrylic acid (AA), 60 g of octadecyl polyoxyethylene methacrylate, and 12 g of laponite are dissolved in 250 mL of water to obtain a solution A. The pH value of the solution A is adjusted to 7 using a 20% by mass sodium hydroxide solution. The solution A is then transferred into a three-necked flask, 0.584 g of potassium persulfate is added, and the reaction is carried out at a constant temperature of 45° C. for 6 h. The reaction product is placed in a vacuum drying oven at a temperature of 60° C. and dried for 1 h. The product is crushed into powder using a crusher to obtain a core material.
[0087] (2) 50 g of the core material prepared in step (1) was mixed with water to prepare a suspension solution with a mass fraction of 20%, and the temperature was raised to 70° C. to allow the core material to fully swell. Then, 15 g of a surfactant CTAB was added. The mixture was stirred at 80° C. and reacted at a rate of 800 r / min for 5 h. After filtration, 20 g of a 0.2 mol / L AgNO3 solution was added to the filtrate to generate a precipitate. The precipitate was dried at 80° C. for 2 h to obtain a modified core material.
[0088] (3) 30 g of the modified core material and 100 g of styrene monomer were added to a four-necked flask, and stirred at a speed of 800 r / min to fully disperse the modified core material in the styrene monomer. Then, stirring was continued at a speed of 800 r / min and 0.2 g of potassium persulfate and 1 g of sodium dodecyl sulfate were added to obtain a stable emulsion. The emulsion polymerization reaction was carried out at a temperature of 75°C and under nitrogen atmosphere protection for 3 hours. Then, 0.1 g of aluminum sulfate was added to the polymerization reaction product under stirring to break the emulsion. The resulting precipitate was washed and dried to obtain the core-shell type thickener material D4.
[0089] Example 5
[0090] This embodiment provides a core-shell sustained-release viscosity increasing agent.
[0091] The preparation method is as follows:
[0092] (1) 80 g of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), 80 g of acrylic acid (AA), 30 g of hexadecyldimethylallylammonium chloride, and 4 g of laponite were dissolved in 250 mL of water to obtain solution A. The pH of solution A was adjusted to 7 using a 20% by mass sodium hydroxide solution. Solution A was then transferred into a three-necked flask, 0.582 g of potassium persulfate was added, and the mixture was reacted at a constant temperature of 45° C. for 4 h. The reaction product was placed in a vacuum drying oven at 60° C. for 3 h, and crushed into powder using a crusher to obtain a core material.
[0093] (2) 50 g of the core material prepared in step (1) was mixed with water to prepare a suspension solution with a mass fraction of 30%, and the temperature was raised to 60° C. to allow the core material to fully swell. Then, 15 g of a surfactant CTAB was added. The mixture was stirred at 80° C. and reacted at a rate of 800 r / min for 4 h. After filtration, 15 g of polyaluminum chloride with a concentration of 0.1 mol / L was added to the filtrate to generate a precipitate. The precipitate was dried at 80° C. for 2 h to obtain a modified core material.
[0094] (3) 40 g of the modified core material and 100 g of styrene monomer were added to a four-necked flask, and stirred at a speed of 800 r / min to fully disperse the modified core material in the styrene monomer. Then, stirring was continued at a speed of 800 r / min and 0.3 g of potassium persulfate and 5 g of sodium dodecyl sulfate were added to obtain a stable emulsion. The emulsion polymerization reaction was carried out at a temperature of 75°C and under the protection of a nitrogen atmosphere for 3 hours. Then, 0.1 g of aluminum sulfate was added to the polymerization reaction product under stirring to break the emulsion. The resulting precipitate was washed and dried to obtain a core-shell type thickener material D5.
[0095] Example 6
[0096] This embodiment provides a core-shell sustained-release viscosity increasing agent.
[0097] The preparation method is as follows:
[0098] (1) 100 g of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), 100 g of acrylic acid (AA), 48 g of hexadecyldimethylallylammonium chloride, and 20 g of laponite were dissolved in 250 mL of water to obtain solution A. The pH of solution A was adjusted to 7 using a 20% by mass sodium hydroxide solution. Solution A was then transferred into a three-necked flask, 0.804 g of ammonium persulfate was added, and the mixture was reacted at a constant temperature of 45° C. for 5 h. The reaction product was placed in a vacuum drying oven at a temperature of 60° C. for 2 h, and crushed into powder using a crusher to obtain a core material.
[0099] (2) 50 g of the core material prepared in step (1) was mixed with water to prepare a suspension solution with a mass fraction of 30%, and the temperature was raised to 60° C. to allow the core material to fully swell. Then, 15 g of a surfactant CTAB was added. The mixture was stirred at 80° C. and reacted at a rate of 800 r / min for 3 h. After filtration, 25 g of a 0.1 mol / L AgNO3 solution was added to the filtrate to generate a precipitate. The precipitate was dried at 80° C. for 2 h to obtain a modified core material.
[0100] (3) 20 g of the modified core material and 100 g of styrene monomer were added to a four-necked flask, and stirred at a speed of 800 r / min to fully disperse the modified core material in the styrene monomer. Then, 0.4 g of potassium persulfate and 5 g of sodium dodecyl sulfate were added at a speed of 800 r / min to obtain a stable emulsion. The emulsion polymerization reaction was carried out at a temperature of 75° C. and under the protection of a nitrogen atmosphere for 3 h. Then, 0.1 g of aluminum sulfate was added to the polymerization product under stirring to break the emulsion. The obtained precipitate was washed and dried to obtain a core-shell type tackifier material D6. The SEM photo of D6 is shown in FIG. Figure 2 , TEM photos see Figure 4 ,from Figure 2It can be seen that the core-shell sustained-release thickener D6 has an obvious core-shell structure and a uniform size of about 1 μm to 5 μm.
[0101] Comparative Example 1
[0102] This comparative example provides a tackifier.
[0103] The preparation method is as follows:
[0104] 100 g of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), 100 g of acrylic acid (AA), 48 g of hexadecyldimethylallylammonium chloride, and 20 g of laponite were dissolved in 250 mL of water to obtain solution A. The pH of solution A was adjusted to 7 using a 20% by mass sodium hydroxide solution. Solution A was then transferred into a three-necked flask, 0.804 g of ammonium persulfate was added, and the mixture was reacted at a constant temperature of 45° C. for 5 h. The reaction product was placed in a vacuum drying oven and dried at 60° C. for 2 h, and then crushed into powder using a crusher to obtain an unmodified nuclear material viscosity enhancer M1.
[0105] Comparative Example 2
[0106] This comparative example provides a tackifier.
[0107] The preparation method is as follows:
[0108] (1) 100 g of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), 100 g of acrylic acid (AA), 48 g of hexadecyldimethylallyl ammonium chloride, and 20 g of laponite were dissolved in 250 mL of water to obtain solution A. The pH of solution A was adjusted to 7 using a 20% by mass sodium hydroxide solution. Solution A was then transferred into a three-necked flask, 0.804 g of ammonium persulfate was added, and the mixture was reacted at a constant temperature of 45° C. for 5 h. The reaction product was placed in a vacuum drying oven at a temperature of 60° C. for 2 h, and then crushed into powder using a crusher to obtain a core material viscosity enhancer.
[0109] (2) 50 g of the core material prepared in step (1) was mixed with water to prepare a suspension solution with a mass fraction of 30%, and the temperature was raised to 60° C. to allow the core material to fully swell. Then, 15 g of a surfactant CTAB was added. The mixture was stirred at 80° C. and reacted at a rate of 800 r / min for 3 h. The mixture was filtered and 20 g of a 0.1 mol / L AgNO3 solution was added to the filtrate to generate a precipitate. The precipitate was dried at 80° C. for 2 h to obtain a modified core material thickener M2.
[0110] Comparative Example 3
[0111] This comparative example provides a tackifier.
[0112] The preparation method is as follows:
[0113] (1) 100 g of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), 100 g of acrylic acid (AA), 48 g of hexadecyldimethylallylammonium chloride, and 24 g of laponite were dissolved in 250 mL of water to obtain solution A. The pH of solution A was adjusted to 7 using a 20% by mass sodium hydroxide solution. Solution A was then transferred into a three-necked flask, 0.804 g of ammonium persulfate was added, and the mixture was reacted at a constant temperature of 45° C. for 5 h. The reaction product was placed in a vacuum drying oven at 60° C. for 2 h, and then crushed into powder using a crusher to obtain a core material.
[0114] (2) 50 g of the core material prepared in step (1) was mixed with water to prepare a suspension solution with a mass fraction of 30%, and the temperature was raised to 60° C. to allow the core material to fully swell. Then, 15 g of a surfactant CTAB was added. The mixture was stirred at 80° C. and reacted at a rate of 800 r / min for 3 h. After filtration, 20 g of a 0.1 mol / L AgNO3 solution was added to the filtrate to generate a precipitate. The precipitate was dried at 80° C. for 2 h to obtain a modified core material.
[0115] (3) 45 g of the modified core material and 100 g of styrene monomer were added to a four-necked flask, and stirred at a speed of 800 r / min to fully disperse the modified core material in the styrene monomer. Then, stirring was continued at a speed of 800 r / min and 0.3 g of potassium persulfate and 5 g of sodium dodecyl sulfate were added to obtain a stable emulsion. The emulsion polymerization reaction was carried out at a temperature of 75°C and under the protection of a nitrogen atmosphere for 3 hours. Then, 0.1 g of aluminum sulfate was added to the polymerization reaction product under stirring to break the emulsion. The resulting precipitate was washed and dried to obtain a core-shell type thickener material M3.
[0116] Comparative Example 4
[0117] This comparative example provides a tackifier.
[0118] The preparation method is as follows:
[0119] (1) 100 g of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), 100 g of acrylic acid (AA), 120 g of hexadecyldimethylallylammonium chloride, and 20 g of laponite were dissolved in 250 mL of water to obtain solution A. The pH of solution A was adjusted to 7 using a 20% by mass sodium hydroxide solution. Solution A was then transferred into a three-necked flask, 0.804 g of ammonium persulfate was added, and the mixture was reacted at a constant temperature of 45° C. for 5 h. The reaction product was placed in a vacuum drying oven at 60° C. for 2 h, and then crushed into powder using a crusher to obtain a core material.
[0120] (2) 50 g of the core material prepared in step (1) was mixed with water to prepare a suspension solution with a mass fraction of 30%, and the temperature was raised to 60° C. to allow the core material to fully swell. Then, 15 g of a surfactant CTAB was added. The mixture was stirred at 80° C. and reacted at a rate of 800 r / min for 3 h. After filtration, 15 g of a 0.1 mol / L AgNO3 solution was added to the filtrate to generate a precipitate. The precipitate was dried at 80° C. for 2 h to obtain a modified core material.
[0121] (3) 45 g of the modified core material and 100 g of styrene monomer were added to a four-necked flask, and stirred at a speed of 800 r / min to fully disperse the modified core material in the styrene monomer. Then, stirring was continued at a speed of 800 r / min and 0.3 g of potassium persulfate and 5 g of sodium dodecyl sulfate were added to obtain a stable emulsion. The emulsion polymerization reaction was carried out at a temperature of 75°C and under the protection of a nitrogen atmosphere for 3 hours. Then, 0.1 g of aluminum sulfate was added to the polymerization reaction product under stirring to break the emulsion. The resulting precipitate was washed and dried to obtain a core-shell type thickener material M4.
[0122] In order to further illustrate the performance of the core-shell sustained-release tackifiers prepared in Examples 1-6 and Comparative Examples 1-4 of the present invention, the following tests were performed.
[0123] (I) The core-shell sustained-release tackifiers D11D6 and M11M4 prepared in Examples 1-6 of the present invention and Comparative Examples 1-4 were respectively subjected to an ATS-TGA-1200Q thermogravimetric analyzer produced by Shanghai Aitisen Instrument Technology Co., Ltd. The samples were heated from room temperature to 300° C. at a heating rate of 10° C. / min in a nitrogen atmosphere. The test environment was consistent. The thermogravimetric curves of the core-shell sustained-release tackifiers D11D6 and M1 to M4 prepared in Examples 1-6 of the present invention and Comparative Examples 1-4 were recorded as follows: Figure 5 and Figure 6 .
[0124] from Figure 5 and Figure 6 It can be seen that the core-shell sustained-release thickeners D11D6 gradually decompose with the increase of temperature, and both show two obvious weight losses. Taking D1 as an example, when the temperature rises to 90°C, the thickener begins to lose weight for the first time, indicating that the shell polystyrene begins to decompose and lose weight. As the temperature continues to rise, the core material gradually decomposes. When the temperature rises to 300°C, 80% of the mass of the core-shell sustained-release thickener has not been decomposed, indicating that the core-shell sustained-release thickener has good high temperature resistance.
[0125] However, when the temperature rises to 60°C, comparative examples M1 and M2 begin to lose weight, indicating that the core material gradually decomposes. When the temperature rises to 300°C, only 40% of the mass of the core-shell sustained-release thickener is not decomposed, indicating that the unmodified or non-core-shell thickener has insufficient high temperature resistance. In addition, when the monomer ratio in the core-shell sustained-release thickener exceeds or falls below the specified range, the temperature resistance of the thickener also decreases (M3 and M4).
[0126] (II) Cement slurry preparation
[0127] Based on the mass of dry oil well cement powder, weigh the solid phase and liquid phase to be added, and prepare cement slurry according to API standard (American Petroleum Institute), wherein the solid phase and the liquid phase are mixed evenly before preparation; pour the weighed liquid phase into the mixer, and set the speed to 4000r·min -1 Pour the weighed solid phase into the mixer within 15 seconds and then adjust the mixer speed to 12000 r / min. -1 , and continue stirring for 35 seconds.
[0128] 1. Sedimentation stability test
[0129] First, set the target temperature of the pressurized thickener to 210℃, the target pressure to 90MPa, and the heating time to 90min. Then immediately put the prepared cement slurry into the kettle of the pressurized thickener. When the temperature and pressure reach the target values, continue to stir the cement slurry at the set temperature and pressure for 30min; slowly release the pressure, and when the temperature drops to 90℃, take out the slurry cup from the thickener, and use a syringe or paper towel to absorb all the residual oil on the upper layer of the cement slurry; use a densitometer to test the density of the upper, middle, and lower parts of the slurry cup.
[0130] Test Example 1
[0131] Density: 2.5g / cm 3 The cement slurry formula is: G-grade cement + 90wt% silica powder + 345wt% iron powder + 10wt% polycarboxylic acid high-temperature retarder + 18wt% AMPS high-temperature fluid loss reducer + 1wt% modified wood sulfonate dispersant + 1wt% tributyl ester defoamer + 1wt% core-shell slow-release viscosity enhancer D1 + 120wt% water, wherein the density of iron powder is 6.0g / cm 3, the system is C1 (in this system, taking the mass of grade G cement as 100%, the amount of silica powder added is 90% of the mass of grade G cement, the amount of iron powder added is 345% of the mass of grade G cement, the amount of polycarboxylic acid high temperature retarder added is 10% of the mass of grade G cement, the amount of AMPS high temperature fluid loss reducer added is 18% of the mass of grade G cement, the amount of modified wood sulfonate dispersant added is 1% of the mass of grade G cement, the amount of tributyl ester defoamer added is 1% of the mass of grade G cement, the amount of core-shell slow-release viscosity enhancer D1 added is 1% of the mass of grade G cement, and the amount of water added is 120% of the mass of grade G cement. The component selection in the cement slurry formula in the following test examples 2-14 is the same as that in test example 1).
[0132] Test Example 2
[0133] Density: 2.5g / cm 3 The cement slurry formula is: G-grade cement + 90wt% silica powder + 345wt% iron powder + 10wt% high-temperature retarder + 18wt% high-temperature fluid loss reducer + 1wt% dispersant + 1wt% defoamer + 2wt% core-shell slow-release thickener D2 + 120wt% water, where the density of iron powder is 6.0g / cm 3 , the system is C2.
[0134] Test Example 3
[0135] Density: 2.5g / cm 3 The cement slurry formula is: G-grade cement + 90wt% silica powder + 345wt% iron powder + 10wt% high-temperature retarder + 18wt% high-temperature fluid loss reducer + 1wt% dispersant + 1wt% defoamer + 3wt% core-shell slow-release viscosity enhancer D3 + 120wt% water, where the density of iron powder is 6.0g / cm 3 , the system is C3.
[0136] Test Example 4
[0137] Density: 2.5g / cm 3 The cement slurry formula is: G-grade cement + 90wt% silica powder + 345wt% iron powder + 10wt% high-temperature retarder + 18wt% high-temperature fluid loss reducer + 1wt% dispersant + 1wt% defoamer + 4wt% core-shell slow-release thickener D4 + 120wt% water, where the density of iron powder is 6.0g / cm 3 , the system is C4.
[0138] Test Example 5
[0139] Density: 2.5g / cm 3The cement slurry formula is: G-grade cement + 90wt% silica powder + 345wt% iron powder + 10wt% high-temperature retarder + 18wt% high-temperature fluid loss reducer + 1wt% dispersant + 1wt% defoamer + 5wt% core-shell slow-release viscosity enhancer D5 + 120wt% water, where the density of iron powder is 6.0g / cm 3 , the system is C5.
[0140] Test Example 6
[0141] Density: 2.5g / cm 3 The cement slurry formula is: G-grade cement + 90wt% silica powder + 345wt% iron powder + 10wt% high-temperature retarder + 18wt% high-temperature fluid loss reducer + 1wt% dispersant + 1wt% defoamer + 1wt% core-shell slow-release viscosity enhancer D6 + 120wt% water, where the density of iron powder is 6.0g / cm 3 , the system is C6.
[0142] Test Example 7
[0143] Density: 2.5g / cm 3 The cement slurry formula is: G-grade cement + 90wt% silica powder + 345wt% iron powder + 10wt% high-temperature retarder + 18wt% high-temperature fluid loss reducer + 1wt% dispersant + 1wt% defoamer + 3wt% core-shell slow-release viscosity enhancer D1 + 120wt% water, where the density of iron powder is 6.0g / cm 3 , the system is C7.
[0144] Test Case 8
[0145] Density: 2.2g / cm 3 The cement slurry formula is: G-grade cement + 90wt% silica powder + 345wt% iron powder + 10wt% high-temperature retarder + 18wt% high-temperature fluid loss reducer + 1wt% dispersant + 1wt% defoamer + 5wt% core-shell slow-release viscosity enhancer D1 + 120wt% water, where the density of iron powder is 6.0g / cm 3 , the system is C8.
[0146] Test Example 9
[0147] Density: 2.5g / cm 3 The cement slurry formula is: G-grade cement + 90wt% silica powder + 345wt% iron powder + 10wt% high-temperature retarder + 18wt% high-temperature fluid loss reducer + 1wt% dispersant + 1wt% defoamer + 120wt% water, where the density of iron powder is 6.0g / cm 3 , the system is C9.
[0148] Test Example 10
[0149] Density: 2.2g / cm 3 The cement slurry formula is: G-grade cement + 90wt% silica powder + 300wt% iron powder + 10wt% high-temperature retarder + 18wt% high-temperature fluid loss reducer + 1wt% dispersant + 1wt% defoamer + 1wt% core-shell slow-release viscosity enhancer D1 + 120wt% water, where the density of iron powder is 6.0g / cm 3 , the system is C10.
[0150] Test Example 11
[0151] Density: 2.5g / cm 3 The cement slurry formula is: G-grade cement + 90wt% silica powder + 345wt% iron powder + 10wt% high-temperature retarder + 18wt% high-temperature fluid loss reducer + 1wt% dispersant + 1wt% defoamer + 3wt% viscosity enhancer M1 + 120wt% water, where the density of iron powder is 6.0g / cm 3 , the system is C11.
[0152] Test Example 12
[0153] Density: 2.5g / cm 3 The cement slurry formula is: G-grade cement + 90wt% silica powder + 345wt% iron powder + 10wt% high-temperature retarder + 18wt% high-temperature fluid loss reducer + 1wt% dispersant + 1wt% defoamer + 3wt% viscosity enhancer M2 + 120wt% water, where the density of iron powder is 6.0g / cm 3 , the system is C12.
[0154] Test Example 13
[0155] Density: 2.5g / cm 3 The cement slurry formula is: G-grade cement + 90wt% silica powder + 345wt% iron powder + 10wt% high-temperature retarder + 18wt% high-temperature fluid loss reducer + 1wt% dispersant + 1wt% defoamer + 3wt% core-shell slow-release viscosity enhancer M3 + 120wt% water, where the density of iron powder is 6.0g / cm 3 , the system is C13.
[0156] Test Case 14
[0157] Density: 2.5g / cm 3 The cement slurry formula is: G-grade cement + 90wt% silica powder + 345wt% iron powder + 10wt% high-temperature retarder + 18wt% high-temperature fluid loss reducer + 1wt% dispersant + 1wt% defoamer + 3wt% core-shell slow-release viscosity enhancer M4 + 120wt% water, where the density of iron powder is 6.0g / cm 3 , the system is C14.
[0158] Table 1 Test results of cement slurry properties described in Test Examples 1-14
[0159]
[0160] It can be seen from the results in Table 1 that when the core-shell sustained-release thickener prepared by the present invention is not added (C9), the density is 2.5 g / cm 3 The cement slurry settled seriously after high temperature curing, and the density difference between the upper and lower parts reached 0.4g / cm 3 The density difference of the cement slurry system added with the core-shell slow-release tackifier prepared in Examples 1-6 of the present invention was improved, and the density difference after curing was less than 0.03 g / cm 3 When the amount of the core-shell slow-release tackifier of the present invention reaches 5wt%, the cement slurry system has basically no sedimentation; in addition, the density is 2.2g / cm 3 The cement slurry system (C10) has no settlement after curing and has good stability;
[0161] However, the cement slurry system to which the viscosity enhancers M1 to M4 prepared in Comparative Examples 1 to 4 of the present invention are added has poor temperature resistance and decomposes in advance, resulting in poor slurry sedimentation stability.
[0162] 2. Thickening curve test
[0163] The cement slurry preparation complies with API standards, the target temperature of the pressurized thickener is 210°C, the target pressure is 90MPa, and the heating time is 90min.
[0164] The thickening performance test of cement slurry is carried out in accordance with the test requirements in GB / T 19139-2012 "Test Methods for Oil Well Cement". Pour the prepared cement slurry into the cylindrical rotating slurry cup of the pressurized thickener, ensure the seal, and set the target temperature and pressure; during the test, the slurry cup rotates at a speed of 150 (±15) r / min, and the instrument measures its torque to obtain the consistency change curve of the cement slurry.
[0165] The thickening curves of the core-shell sustained-release thickener D1 prepared in Example 1 of the present invention with and without the addition of the core-shell sustained-release thickener D1 are shown in FIG. Figure 6 and Figure 7 As shown, the thickening curve of the cement slurry system (C9) without the core-shell slow-release tackifier D1 prepared in Example 1 gradually decreases with increasing temperature, and the viscosity decreases significantly; the thickening curve of the cement slurry system (C7) with the core-shell slow-release tackifier D1 prepared in Example 1 does not change significantly with increasing temperature, indicating that the core material has a significant thickening effect at this temperature, and the core-shell slow-release tackifier D1 has a temperature resistance of up to 210°C, which is consistent with the results of the thermogravimetric curve.
[0166] The thickening curve of the cement slurry system (C11) to which the layered tackifier M1 prepared in Comparative Example 1 of the present invention is added is as follows: Fig. 9As shown, the thickening curve of the cement slurry system (C11) to which the viscosity enhancer M1 described in comparative example 1 is added, it can be seen that the initial viscosity of the thickening curve after adding M1 is too large, resulting in an unstable thickening curve, so it is easy to decompose without a shell structure and has poor temperature resistance.
[0167] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A core-shell sustained-release thickener, characterized in that: The invention comprises a core material and a shell material, wherein the core material is prepared from a raw material I comprising 2-acrylamide-2-methylpropane sulfonic acid, acrylic acid, a hydrophobic monomer and laponite; and the shell material is prepared from a raw material II comprising a styrene monomer.
2. The core-shell sustained-release thickener according to claim 1, characterized in that: The mass ratio of 2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, hydrophobic monomer and laponite is (25-60): (20-50): (10-20): (1-5); And / or, the hydrophobic monomer is selected from at least one of isooctyl acrylate, octadecyl acrylate, octadecyl polyoxyethylene methacrylate, behenyl polyoxyethylene ether methacrylate and hexadecyl dimethyl allyl ammonium chloride.
3. The core-shell sustained-release thickener according to claim 1 or 2, characterized in that: The raw material I further includes a first initiator; preferably, the first initiator is selected from at least one of ammonium persulfate and potassium persulfate; And / or, the raw material II also includes an emulsifier, a second initiator and a demulsifier; preferably, the emulsifier is selected from at least one of sodium dodecyl sulfate, sodium dodecyl sulfonate, and hexadecyltrimethylammonium bromide; the second initiator is selected from at least one of ammonium persulfate and potassium persulfate; the demulsifier is selected from at least one of aluminum sulfate, calcium chloride, and magnesium chloride.
4. A method for preparing the core-shell sustained-release tackifier according to any one of claims 1 to 3, characterized in that: The steps include: 1) mixing raw material I with water, and performing reaction I to obtain a core material; 2) The core material obtained in step 1) is mixed with styrene monomer, and reacted in an inert atmosphere to obtain the core-shell sustained-release tackifier.
5. The preparation method according to claim 4, characterized in that: In step 1), the ratio of raw material I to water is (184-292) g: 250 mL; and or, the mixing obtains solution A, and uses a pH regulator to adjust the pH of solution A to 7; preferably, the pH regulator is selected from at least one of a sodium hydroxide solution and a potassium hydroxide solution with a mass fraction of 10% to 30%; And / or, a first initiator is further added to the reaction I; preferably, the amount of the first initiator added is 0.1% to 0.5% of the total mass of the raw material I; And / or, the conditions of the reaction I include: temperature of 30°C to 60°C, time of 2h to 10h; And / or, the reaction I further includes drying and crushing.
6. The preparation method according to claim 4 or 5, characterized in that: In step 2), the mass of the core material is 20% to 50% of the mass of the styrene monomer; And / or, an emulsifier and a second initiator are further added to the reaction II; preferably, the amount of the emulsifier added is 1% to 8% of the mass of the styrene monomer; the amount of the second initiator added is 0.1% to 0.5% of the mass of the styrene monomer; And / or, after the reaction II, a demulsifier is further added; preferably, the amount of the demulsifier added is 0.05% to 0.2% of the mass of the styrene monomer; And / or, the conditions of reaction II include: reaction temperature of 70°C to 80°C, reaction time of 2h to 5h; And / or, the inert atmosphere is selected from nitrogen.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The core material further comprises a modification step; preferably, the modification step comprises adding a surfactant to the core material aqueous solution, and performing reaction III to obtain a modified core material.
8. The preparation method according to any one of claims 4 to 7, characterized in that: The mass fraction of the core material being water soluble is 10% to 50%; And / or, the amount of the surfactant added is 10% to 40% of the mass of the core material; preferably, the surfactant is selected from at least one of sodium dodecyl sulfate, sodium dodecyl sulfonate, hexadecyltrimethylammonium bromide, sodium hexadecyl sulfonate, and sodium hexadecylbenzene sulfonate; And / or, the core material aqueous solution further comprises a heating step; preferably, the heating temperature is 50° C. to 70° C.; And / or, the conditions of reaction III include: reaction temperature of 80° C., reaction time of 2 h to 5 h.
9. The preparation method according to any one of claims 4 to 8, characterized in that: After the reaction III, the step of filtering the reaction liquid, adding a precipitant to the filtrate to generate a precipitate, and drying the precipitate is also included; preferably, the amount of the precipitant added is 30% to 50% of the mass of the core material; further preferably, the precipitant is at least one of an AgNO3 solution and a polyaluminium chloride solution; further preferably, the concentration of the AgNO3 solution or the concentration of the polyaluminium chloride solution is 0.05 mol / L to 0.2 mol / L.
10. Use of the core-shell slow-release tackifier according to any one of claims 1 to 3 or the core-shell slow-release tackifier prepared by the preparation method according to any one of claims 4 to 9 in oil and gas well cementing. Preferably, the core-shell slow-release tackifier is used as a suspension stabilizer in high-density cement slurry for oil and gas well cementing. More preferably, the addition amount of the core-shell slow-release tackifier in the high-density cement slurry is 1% to 5% based on the total mass of cement.
Citation Information
Patent Citations
Polymer material, preparation method thereof and well cementation cement slurry system
CN114181352A
Delayed organic tackifying stabilizer for well cementation as well as preparation method and application of delayed organic tackifying stabilizer
CN115124980A
Delayed inorganic tackifying stabilizer for well cementation and preparation method thereof
CN115124985A
A core-shell polymer powder
EP0654454A1